LIGETI’S ROMANIAN CONCERTO: FROM WAX CYLINDERS TO SYMPHONY ORCHESTRA - Bianca ŢIPLEA TEMEŞ (Studia Universitatis Babeş-Bolyai. Musica)
Beneath the Romanian Concerto’s colourful orchestral surface, evoking the folk-inspired music of both Bartók and Enescu, lies Ligeti’s early activity as a researcher (1949-1950) at the Folklore Institute in Bucharest. Placing cutouts from the printed score side by side with the manuscripts of his transcriptions kept at the Paul Sacher Foundation, one may discover this piece’s origins, and the process by which Ligeti, the “archaeologist” brought the rich stock of Romanian folk music from the wax cylinders to the symphony orchestra. Romanian Concerto not only shows the impact our folk music had on the young Ligeti but also the way in which his collaboration with Romanian ethnomusicologists such as Mircea Chiriac influenced the composition of his first major orchestral piece.